Síndrome de COVID-19 persistente en pacientes hospitalizados en el Hospital Regional de Loreto durante el período 2021- 2022 - Callpa Saldaña, Karina (2025)
GENERAL OBJECTIVE: To evaluate the characteristics associated with persistent COVID-19 syndrome in patients hospitalized at the Regional Hospital of Loreto during the period 2021-2022. MATERIALS AND METHODS: Observational, correlational study that evaluated 139 medical records randomly. Cases of patients hospitalized for COVID19 without a diagnosis of sequelae that meet the inclusion criteria will be analyzed. Data will be reported in double-entry tables and proportions tests using the SPSS v25 statistical package. CONCLUSIONS: During the evolution of the pandemic, it has been shown that SARS-COV-2 has generated long-term consequences in patients who have suffered from the disease, especially in cases of hospitalized patients. There are persistent symptoms that characterize COVID-19 patients seen in our hospital during the pandemic.